Connotative Meaning of L.A. Bold Cigarette Advertisement My Kind of Bold Version - Alki Galang M. Putra; Laila Ulsi Qodriani (Universitas Teknokrat Indonesia, 2017)
This study concerns on the connotative meaning in L.A. Bold cigarette TV version advertisement. The objectives of the research are to find out connotative meaning and to describe how connotative meaning denoted in the advertisement. Regarding to this, the writers applied theory of Connotative of a Denotative Sign from Roland Barthes consisting of E, an expression (or signifier), in relation (R) to C, a content (or signified): E R C. The data and data source of this study are the text and pictures that appear in the whole advertisement. As the result, it concludes that each sign has a sign system creates connotative meaning. It is found 16 connotative meanings from 7 data, they are Good Carrier, Enjoyment and Challenge, High class, Masculine and Classic, Playboy and Glamour, Metropolitan, Modern, Masculine, Sporty, Brave, Risk Taker, and not be afraid to smoke cigarette.